TINJAUAN YURIDIS TERHADAP IMPLEMENTASI PAJAK PROGRESIF PADA SISTEM PERPAJAKAN DI INDONESIA - Rojikin, Umar; Padhilah, Piqi Rizki; Najmudin, Nandang (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The implementation of progressive taxation within Indonesia’s tax system is a state initiative aimed at realizing social justice by levying taxes based on the taxpayer's economic capacity. Progressive tax imposes increasing rates in line with rising income, or the number of taxable objects owned, meaning that high-income individuals are taxed more than those with lower incomes. This concept is applied to various tax types, including Income Tax (PPh) and Motor Vehicle Tax (PKB), both of which are regulated under national legislation such as Law Number 36 of 2008 on Income Tax and Law Number 28 of 2009 on Regional Taxes and Regional Levies. This study aims to analyze the legal foundations and underlying principles of the progressive tax system in Indonesia. The research method used is a normative juridical review, which involves examining relevant statutory regulations, legal literature, and official legal documents. The findings indicate that the implementation of progressive taxation aligns with the principles of justice and legality within tax law. Furthermore, this policy supports the goals of income redistribution and strengthens the role of the state in establishing a fair, transparent, and accountable tax system. Therefore, progressive tax serves not only as a revenue collection mechanism but also as a crucial instrument of social policy.